ANTIOXIDANT AND ANTI-INFLAMMATORY EFFECTS OF RHAMNAZIN ON LIPOPOLYSACCHARIDE-INDUCED ACUTE LUNG INJURY AND INFLAMMATION IN RATS - Wu, GuoRong; Dai, XiaoPing; Li, XiangRong; Jiang, HePing (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Acute Lung Injury (ALI) results into severe inflammation and oxidative stress to the pulmonary tissue. Rhamnazin is a natural flavonoid and known for its antioxidant and anti-inflammatory properties. Materials and methods: The antioxidative and anti-inflammatory properties rhamnazin were tested for protection against the acute lung injury. We investigated whether rhamnazin improves the lipopolysaccharide (LPS)-induced ALI in an animal model (rat). We also studied the probable molecular mechanism of action of rhamnazin. Rhamnazin was injected intraperitoneally (i.p.) (5, 10 and 20 mg/kg) two days before intratracheal LPS challenge (5mg/kg). The changes in lung wet-to-dry weight ratio, LDH activity, pulmonary histopathology, BALF protein concentration, MPO activity, oxidative stress, cytokine production were estimated. Results: The results showed a significant attenuation of all the inflammatory parameters and a marked improvement in the pulmonary histopathology in the animal groups pretreated with rhamnazin. The rhamnazin pretreated group also showed activation of Nrf2 pathway and attenuation of ROS such as H2O2, MDA and hydroxyl ion. These results indicated that rhamnazin could attenuate the symptoms of ALI in rats due to its strong antioxidant and anti-inflammatory properties. Conclusion: The results strongly demonstrated that rhamnazin provides protection against LPS-induced ALI. The underlying mechanisms of its anti-inflammatory action may include inhibition of Nrf2 mediated antioxidative pathway.